Effects of Li+ conduction on the capacity utilization of cathodes in all-solid-state lithium batteries - Wang, Zhiping; Song, Shipai; Jiang, Chunzhi; Wu, Yongmin; Xiang, Yong; Zhang, Xiaokun (Frontiers in Chemistry, 2023)
The Li+ conduction in all-solid-state lithium batteries is limited comparing with that in lithium-ion batteries based on liquid electrolyte, because of the lack of the infiltrative network for Li+ transportation. Especially for the cathode part, the practically available capacity is constrained due to the limited Li+ diffusivity. Herein, all-solid-state thin-film lithium batteries based on LiCoO2 thin-films with varying thicknesses were fabricated and tested. Although an area capacity as high as 1.2 mAh/cm2 was achieved when the thickness of cathode thin-film reached 25.7 μm, the available capacity of cathode materials was only 65.6% of the expected value. The influence of limited Li+ conduction on the capacity utilization of cathode was analyzed using a one-dimensional model of the fabricated batteries. The uneven Li distribution in cathode thin-films owing to the restricted Li+ diffusivity was revealed. Importantly, the characteristic size for cathode with varying Li+ diffusivity, which would not constrain the available capacity, was explored to guide the cathode material development and cell design of all-solid-state lithium batteries.